MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INGGRIS SISWA MENGGUNAKAN MODEL PEMBELAJARAN RUNNING DICTATION - Adawiyah, Wilda Nur Aeni; Mangkuwibawa, Hilman; Rifqi Mahmud, Muhammad (Jurnal Pendidikan Dasar dan Keguruan, 2023)
This research aims to improve students' speaking skills using the Running Dictation learning model. This research was motivated by problems that had been discovered from the results of a preliminary study in the learning process when students spoke English. That the students' speaking skills do not meet the KKM set by the school, namely 75. The research method used is classroom action research (PTK) with three cycles in which each cycle contains two actions. The subjects of this research were 25 class VI students at MI Integrated Ar-Rifqi. The data collection techniques used are performance tests and observation. The speaking skills of class VI MI Integrated Ar-Rifqi students before being given action achieved 32% classical completeness in the poor category. After taking action in cycle I, an average score of 66 was obtained with classical completeness of 54%, in cycle II there was an increase with an average score of 74 with classical completeness of 71% and in cycle III the score was obtained. an average of 81 with a classical completion score of 84%. Based on classical completeness, overall this research has reached ≥75% of the number of students who achieved the KKM, namely 84%. Thus, it shows that students' speaking skills after implementing the Running Dictation model in English learning have improved.